Locally activated semisynthetic fluorescent biosensors for imaging cellular biochemistry - Coïs, Justine; Dumat, Blaise (Comptes Rendus. Chimie)
Biosensors based on fluorescent proteins are widely used as genetically encoded indicators due to their capacity to target various biological analytes (metal ions, reactive oxygen species, biomolecules, etc.) within cells with precise localization. However, their complex development associated with the lack of photophysical versatility constrains the scope of their application in biosensing. Alternatively, semisynthetic fluorescent biosensors that combine a small chemical indicator with a self-labeling protein tag benefit from the versatility of molecular engineering and from the selectivity of genetic encoding of the recombinant protein. The variations in photophysical properties of the chemical indicator upon analyte recognition provide high sensitivity and rapid response time, making them attractive alternatives for biosensing. Fluorogenic semisynthetic biosensors that are fluorescent only upon local activation by reaction with a genetically encoded self-labeling protein tag provide an additional level of selectivity, allowing wash-free imaging experiments. This minireview focuses on the latter class of hybrid sensors and provides an outlook on the different small molecular probe design strategies and self-labeling protein tag combinations (mostly SNAP-tag and HaloTag) for their construction. The authors expect to present new clues and ideas to researchers for further advances in this field.